Low-dose Esketamine combined with Propofol in microscopic pediatric strabismus surgery: a randomized controlled study - Yaping Shen; Bo Shi; Yu Mo; Junhe Wu; Zhentao Sun (BMC Anesthesiology)
Abstract Objective To observe the effect of low-dose esketamine combined with propofol in pediatric strabismus surgery. Methods A total of 84 children aged 3–15 years, regardless of gender, with a BMI of 13–26 kg/m2, ASA grade I or II, were selected for elective microscopic strabismus surgery and divided into two groups based on the randomized numerical table: esketamine group (group E) and propofol group (group C), with 42 patients in each group. Group E was pre-injected with esketamine 0.2 mg/kg, and propofol 2.5 mg/kg was slowly injected after one minute. Group C was pre-treated with an equal volume of saline, and propofol 2.5 mg/kg was administered slowly after one minute. The occurrence of propofol injection pain was assessed using the Verbal Rating Scale (VRS). HR and MAP were recorded in the two groups at 5 min before induction, after induction, at the start of the procedure, and at the end of the procedure. operative time, extubation time and post-anesthesia care unit (PACU) stay were recorded. The Pain Behaviour Scale for Children (Face, Legs, Activity, Cry, Consolability, FLACC) scores at the time of discharge from the PACU and at 1day, 3days and 7days postoperatively were recorded. perioperative tachycardia, emergence agitation, oculocardiac reflex, extubation cough and other adverse reactions were also recorded. Results Compared with Group C, Group E exhibited significantly lower rates of propofol injection pain(cases (%), 87.5% VS 56.1%, P = 0.002), and moderate-to-severe pain during induction(75.0% VS 24.4%, P<0.001), reduced FLACC scores at PACU discharge(median and interquartile spacing [M(IQR)], 3.50(4) VS 3.00(2), P = 0.039) and 1 day postoperatively(M(IQR), 5.00(3) VS 3.00(2), P<0.001), and decreased incidences of adverse events including emergence agitation(32.5% VS 12.2%, P = 0.028), oculocardiac reflex(35.0% VS 14.6%, P = 0.034), and extubation cough(25.0% VS 7.3%, P = 0.030). However, no statistically significant differences were observed between the two groups in operative duration, extubation time, PACU stay duration, FLACC scores at 3 and 7 days postoperatively, or heart rate and mean arterial pressure at any measured time point. Conclusion General anesthesia with low-dose esketamine combined with propofol for pediatric strabismus correction surgery effectively alleviates propofol injection pain, reduces FLACC scores at PACU discharge and 1 day postoperatively, and decreases the incidence of adverse reactions such as emergence agitation, oculocardiac reflex, and extubation cough, demonstrating its safety for use in this procedure. Trial registration This study was approved by the Scientific Research and Clinical Trials Ethics Committee of The First Affiliated Hospital of Zhengzhou University (Approval No. 2023-KY-1509), registered in the Chinese Clinical Trial Registry (Registration No. ChiCTR2400092266, registration date on 11/13/2024).